GH4169 high-temperature alloy bar as well as preparation method and application thereof
Through triple smelting, two homogenization treatments and cold drawing process, the rolling parameters of GH4169 high-temperature alloy bars are controlled, the problem of insufficient grain size of small-sized GH4169 alloy bars is solved, and the preparation of GH4169 high-temperature alloy bars with excellent high-temperature performance is achieved.
Patent Information
- Application Number
- CN202510973424.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-09-26
AI Technical Summary
The existing process makes it difficult to prepare small-sized GH4169 high-temperature alloy bars with uniform structure, no mixed crystals and grain size of 6 to 9, resulting in insufficient performance at high temperatures.
GH4169 high-temperature alloy bars with uniform structure are produced by adopting triple smelting process, two homogenization treatments, forging, hot rolling and cold drawing processes, controlling rolling temperature, deformation amount and speed.
The grain size of GH4169 high-temperature alloy rods is stably controlled at level 7 to 8, the room temperature tensile strength is ≥1300 MPa, the high-temperature tensile strength at 650℃ is ≥1000 MPa, and the high-temperature endurance time is ≥23 h, meeting the high-temperature performance requirements of aerospace fasteners.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of deformed high-temperature alloy processing, in particular to a GH4169 high-temperature alloy bar and a preparation method and application thereof. Background Art
[0002] GH4169 high-temperature alloy is a precipitation-strengthened nickel-based high-temperature alloy with body-centered cubic γ' and face-centered cubic γ'' as strengthening phases. It has excellent comprehensive mechanical properties in the temperature range of -253~700℃. The yield strength below 650℃ ranks first among deformable high-temperature alloys. It also has good fatigue resistance, radiation resistance, oxidation resistance, corrosion resistance, and good processing performance.
[0003] Small-sized GH4169 superalloy bars (φ8 mm to φ12 mm) are primarily used in the manufacture of aerospace fasteners, primarily at high temperatures. To ensure the reliability of connected components, higher requirements are placed on the high-temperature performance and microstructure uniformity of the GH4169 superalloy bars produced by metallurgical plants. In particular, users have requested a grain size of 6-9 for small-sized GH4169 alloy bars used in fastener production. This is because grain boundaries are weak links during high-temperature deformation and fracture exhibits intergranular fracture characteristics. Therefore, by appropriately increasing the grain size, the grain boundary area can be reduced, minimizing the channels for intergranular expansion, thereby improving high-temperature performance. However, due to the small size of the existing GH4169 alloy rolled bars, the thermal deformation during the rolling process is in a single elongation direction. This results in a very rapid temperature drop and large deformation during rolling, resulting in a grain size of more than 10 levels in the produced GH4169 alloy bars and severe carbide segregation in the strips. Furthermore, the internal energy of the bars after rolling is high. If the residual stress within the bars cannot be released after heat treatment, an unrecrystallized grain structure will form. This banding segregation can also easily cause a mixed crystal structure in the rolled bars, resulting in a grain size that cannot meet the needs of users for higher-end applications. Therefore, it is necessary to find a rationally controlled production process that can achieve moderate internal stress in the as-rolled structure, without striping segregation, and produce a fully recrystallized, uniform grain structure with a grain size of 6 to 9 levels after heat treatment. Summary of the Invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a GH4169 high-temperature alloy rod and its preparation method and application. The preparation method provided by the present invention can prepare small-sized GH4169 high-temperature alloy rods with uniform structure, no mixed crystals, no obvious stripe segregation, and grain size of 6 to 9.
[0005] The present invention provides a method for preparing a GH4169 high-temperature alloy bar, comprising the following steps:
[0006] S1) sequentially subjecting a GH4169 high-temperature alloy ingot to a first homogenization treatment, forging, a second homogenization treatment, and hot rolling to obtain a billet;
[0007] S2) performing a first heat rolling and a second heat rolling on the billet obtained in step S1) to obtain a billet;
[0008] The second-pass rolling specifically comprises: holding the billet after the first-pass rolling at a temperature of 1020° C. to 1100° C. for 30 min to 40 min and then rolling it; the total deformation of the second-pass rolling is 60% to 75%, the second-pass rolling time is within 40 s, the second-pass rolling speed is 1.4 m / s to 1.8 m / s, and the final rolling temperature of the second-pass rolling is above 1000° C.;
[0009] S3) subjecting the bar blank obtained in step S2) to solution treatment, primary cold drawing, and aging treatment in sequence to obtain a GH4169 high-temperature alloy bar;
[0010] The drawing rate of the primary cold drawing is 45 mm / s to 55 mm / s, and the deformation of the primary cold drawing is 5% to 10%.
[0011] The present invention first subjects a GH4169 high-temperature alloy ingot to a first homogenization treatment, followed by forging, a second homogenization treatment, and hot rolling to produce a blank. The GH4169 high-temperature alloy ingot is obtained by sequentially subjecting the smelted raw materials to vacuum induction melting, electroslag remelting, and vacuum consumable remelting. The ingot produced by the triple smelting process of vacuum induction melting, electroslag remelting, and vacuum consumable remelting has a dense structure, low impurity element content, and is less susceptible to macrosegregation and metallurgical defects.
[0012] The present invention first subjects the GH4169 high-temperature alloy ingot to a first homogenization treatment. Specifically, the first homogenization treatment involves maintaining the ingot at 1140°C to 1160°C for 10 to 24 hours, then raising the temperature to 1180°C to 1200°C and maintaining it for 24 to 72 hours. After the first homogenization treatment, the resulting ingot is forged; the forging is preferably multi-fire forging, with the initial forging temperature being no less than 1080°C and the final forging temperature being no less than 950°C. After forging, the present invention further includes air cooling the resulting billet. After forging, the billet undergoes a second homogenization treatment, specifically maintaining the billet at 1170°C to 1190°C for 10 to 20 hours. The present invention utilizes two homogenization treatments and forging, resulting in a uniform composition across the cross-section of the resulting billet, ensuring that the finished small-sized bars produced after subsequent rolling are free of stripe segregation. The present invention does not impose any requirements on the deformation amount of the forging, as long as it is ensured that there is no cracking during the forging process and the steel is forged to a size that can enter the rolling mill.
[0013] After the second homogenization treatment, the ingot obtained after the second homogenization treatment is subjected to hot rolling to produce a billet; the temperature and deformation of the hot rolling are not particularly limited. After the hot rolling, the present invention further includes air cooling the billet obtained after the hot rolling. The billet obtained after the hot rolling is preferably a billet with a square size of 45 mm to 55 mm (meaning that the cross-section of the billet is a square with a side length of 45 mm to 55 mm).
[0014] In certain embodiments of the present invention, the present invention first sequentially subjects the smelting raw materials to vacuum induction melting, electroslag remelting, and vacuum consumable remelting to obtain a GH4169 high-temperature alloy ingot with a diameter of φ406 mm to φ550 mm; then the GH4169 high-temperature alloy ingot is subjected to the above-mentioned first homogenization treatment, and the obtained ingot is forged to obtain a 130 mm square billet; then the billet is subjected to a second homogenization treatment, and the obtained ingot is hot rolled to obtain a 45 mm square to 55 mm square billet.
[0015] After obtaining the billet, the present invention sequentially performs the first fire rolling and the second fire rolling on the billet to obtain the bar billet. Specifically, the temperature of the first fire rolling of the present invention is not particularly limited; the deformation amount is also not particularly limited. According to the size of the billet obtained after hot rolling, it is ensured that the billet can still meet the deformation amount requirement of the second fire rolling after the first fire rolling; after the first fire rolling, the present invention keeps the billet after the first fire rolling at a temperature of 1020℃~1100℃ for 30 min~40 min and then rolls it to avoid overburning of the billet; the total deformation amount of the second fire rolling is controlled to 60%~75%, and the speed of the second fire rolling is controlled to 1.4 m / s~1.8 m / s, and at 40 s, and ensure that the final rolling temperature of the second rolling is above 1000°C to obtain a bar billet; the present invention adopts a two-pass rolling process to roll the obtained billet in sequence, and the grain size of the obtained bar billet is made more uniform through multiple rolling passes. By accurately controlling the deformation amount, rolling temperature, rolling speed and rolling time of the hot rolling final pass, the grain size of the bar is controlled to be 7 to 8 levels, and the structure is uniform.
[0016] After obtaining the rod blank, the present invention sequentially performs solution treatment, primary cold drawing and aging treatment on the obtained rod blank to obtain GH4169 high-temperature alloy rod. The present invention preferably obtains GH4169 high-temperature alloy rods with specifications of φ8 mm~φ12 mm. The primary cold drawing described in the present invention is the same as that described above and will not be repeated here. The temperature of the solution treatment described in the present invention is 950℃~980℃, and the time of the solution treatment is 50 min~70 min; the aging treatment is specifically: keeping warm at 700℃~750℃ for 7 h~9 h, cooling to 600℃~650℃ at a cooling rate of 45℃ / s~55℃ / s and keeping warm for 7 h~9 h. The present invention subjects the obtained bar blank to a solution treatment, then uses a fixed die drawing machine to perform a small deformation cold drawing, and finally performs an aging treatment. Different from the prior art in which the hot-rolled bar blank is directly subjected to the solution treatment and aging treatment, the present invention does not change the grain size of the hot-rolled bar by controlling the small deformation amount of cold working and the drawing rate, and improves the mechanical properties and surface quality of the alloy bar through the work hardening of cold deformation.
[0017] In certain embodiments of the present invention, the present invention sequentially performs first and second heat rolling on the obtained 45 mm square to 55 mm square billet to obtain a bar billet with a specification of approximately φ8 mm to φ12 mm, and sequentially performs solid solution treatment, primary cold drawing and aging treatment on the obtained bar billet to obtain a GH4169 high-temperature alloy bar with a specification of φ8 mm to φ12 mm.
[0018] The GH4169 high-temperature alloy bar of the present invention comprises the following components in percentage by weight:
[0019] C: 0.015%~0.060%; Si: ≤0.35%; Mn: ≤0.35%; P: ≤0.015%; S: ≤0.002%; Cr: 17.00%~21:00%; Mo: 2.80%~ 3.30%; Al: 0.30%~0.70%; Ti: 0.75%~1.15%; Nb: 5.00%~5.50%; Ni: 50.00%~55.00%; B: 0.002%~0.006 %; Cu: ≤0.30%; Co: ≤1.00%; Ta: ≤0.10%; Bi: ≤0.00003%; Pb: ≤0.0005%; Sn: ≤0.005%; Se: ≤0.0003%; Ag: ≤0.0005%; Te: ≤0.00005%; TI: ≤0.0001%; Mg: ≤0.005%; Ca: ≤0.005%; O: ≤0.005%; N: ≤0.01%; the balance is Fe.
[0020] The present invention also provides GH4169 high-temperature alloy bars produced by the preparation method described in any of the above technical solutions. The GH4169 alloy bars produced by the present invention have a grain size controlled at level 7 to 8, a room temperature tensile strength of ≥1300 MPa, a high-temperature tensile strength of ≥1000 MPa at 650°C, a high-temperature endurance of ≥23 h at 650°C / 690 MPa, and a high-temperature endurance elongation of ≥5%. This successfully addresses the problem of currently available technologies producing small-sized GH4169 alloy bars with excessively fine grains that fail to meet user requirements.
[0021] The present invention also provides an aerospace fastener, which is made from the GH4169 high-temperature alloy bar prepared by any of the above-described technical solutions. This aerospace fastener, processed from the GH4169 alloy bar provided by the present invention, ensures the reliability of the aerospace fastener as a connecting component due to the excellent high-temperature performance and microstructure uniformity of the GH4169 high-temperature alloy bar.
[0022] The present invention provides a GH4169 high-temperature alloy bar, its preparation method, and application. The preparation method provided by the present invention utilizes a triple smelting, two homogenization treatments, forging, hot rolling, and cold drawing process to produce a GH4169 high-temperature alloy bar. The resulting bar can be as small as 8 mm to 12 mm in diameter, exhibiting uniform microstructure from center to edge without stripe segregation. The grain size can be stably controlled at 7 to 8 levels, i.e., the grain size is between 20 μm and 30 μm, with a grade difference of ≤1 level and no mixed crystals. The bar also exhibits room temperature tensile strength ≥1300 MPa, high-temperature tensile strength at 650°C ≥1000 MPa, high-temperature endurance at 650°C / 690 MPa ≥23 h, and high-temperature endurance elongation ≥4%. The bar exhibits excellent overall mechanical properties, resolving technical issues encountered in existing processes for producing small-sized GH4169 alloy bars, such as grain size exceeding 10 levels, excessively fine grains, and the tendency to develop mixed crystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the carbide distribution diagram of the φ11.6 mm rod prepared in Example 1 of the present invention;
[0024] Figure 2 This is the grain size center distribution diagram of the φ11.6 mm rod prepared in Example 1 of the present invention;
[0025] Figure 3 This is the grain size edge distribution diagram of the φ11.6 mm rod prepared in Example 1 of the present invention;
[0026] Figure 4 This is the carbide distribution diagram of the φ9.1 mm rod prepared in Example 2 of the present invention;
[0027] Figure 5 This is the grain size center distribution diagram of the φ9.1 mm rod prepared in Example 2 of the present invention;
[0028] Figure 6 This is the grain size edge distribution diagram of the φ9.1 mm rod prepared in Example 2 of the present invention;
[0029] Figure 7 This is the carbide distribution diagram of the φ11 mm rod prepared in Comparative Example 1 of the present invention;
[0030] Figure 8 This is a grain size center distribution diagram of the φ11 mm rod prepared in Comparative Example 1 of the present invention;
[0031] Figure 9 This is the grain size edge distribution diagram of the φ11 mm rod prepared in Comparative Example 1 of the present invention;
[0032] Figure 10This is the grain size edge distribution diagram of the φ10.5 mm rod prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The present invention discloses a GH4169 high-temperature alloy bar, a preparation method thereof, and an application thereof. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters for implementation. It should be particularly noted that all similar replacements and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications herein without departing from the content, spirit, and scope of the present invention to implement and apply the technology of the present invention.
[0034] The present invention will be further described below with reference to the embodiments:
[0035] Example 1
[0036] The present embodiment provides a 11.6 mm diameter small-size GH4169 high-temperature alloy bar, which includes the following components and their weight percentages: C: 0.031%; Si: 0.08%; Mn: 0.005%; P: 0.0062%; S: 0.0009%; Cr: 19.03%; Mo: 3.16%; Al: 0.673%; Ti: 0.904%; Nb: 5.10%; Ni: 51.12%; B: 0.0041%; Cu: 0.0072%; Co: 0.005%; Ta: 0.0042%; Bi: 0.00001%; Pb: 0.0001%; Sn: 0.0001%; Se: 0.0001%; Ag: 0.0001%; Te: 0.00001%; TI: 0.0005%; Mg: 0.001%; Ca: 0.001%; O: 0.0007%; N: 0.0061%; the balance is Fe.
[0037] The above-mentioned small-sized GH4169 high-temperature alloy bars are prepared by the following method: batching → vacuum induction melting → electroslag remelting → vacuum consumable remelting → ingot homogenization → ingot surface treatment to obtain qualified ingots; then forging → homogenization → hot rolling → hot rolling → solution annealing → primary cold drawing → finished product heat treatment → polishing and straightening → non-destructive testing.
[0038] The specific steps are as follows:
[0039] S1: A GH4169 high-temperature alloy ingot with an ingot diameter of φ406 mm was obtained by a triple smelting process of vacuum induction + electroslag remelting + vacuum consumable remelting;
[0040] S2: The GH4169 alloy ingot obtained in S1 was homogenized in a natural gas furnace by holding at 1150°C for 20 h and then heating to 1190°C for 30 h.
[0041] S3: The alloy ingot after S2 homogenization treatment is forged with an initial forging temperature of 1100°C and a final forging temperature of 955°C. After multiple forgings, a 130 mm square billet is finally obtained, which is then air-cooled.
[0042] S4: The billet after S3 forging is subjected to secondary homogenization treatment, the homogenization temperature is 1170℃, and the holding time is 15 h;
[0043] S5: hot rolling the billet obtained in step S4 to form a hot rolled billet of 55 mm square;
[0044] S6: The billet obtained in S5 is rolled in two passes using a horizontal rolling mill, with each pass being rolled in multiple passes. In the first pass, the billet is rolled from 55 mm square to φ21 mm. In the second pass, the billet is heated to a holding temperature of 1080°C for 30 min, followed by hot rolling. The total deformation is 67%, the rolling line speed is controlled at 1.75 m / s, the final rolling time is 35 s, the final rolling temperature is 1012°C, and the billet is air-cooled after final rolling to obtain a hot-rolled billet with a specification of φ12 mm.
[0045] S7: S6 was rolled into a semi-finished hot-rolled bar of φ12 mm in a solution furnace, held at 960°C for 60 min, air-cooled, and then cold-drawn once using a fixed-die drawing machine at a drawing rate of 50 mm / s and a cold drawing deformation of 6.5% to obtain a φ11.6 mm bar. The φ11.6 mm bar was aged by holding at 720°C for 8 h, then cooling at a rate of 50°C / s to 620°C, holding at 620°C for 8 h, and air-cooling.
[0046] The final φ11.6 mm rods were tested for carbide, grain size, room temperature and high temperature properties. Figures 1 to 3 As shown, Figure 1 This is the carbide distribution diagram of the φ11.6 mm rod prepared in Example 1 of the present invention. Figure 2 This is the grain size center distribution diagram of the φ11.6 mm rod prepared in Example 1 of the present invention. Figure 3 This is the grain size edge distribution diagram of the φ11.6 mm rod prepared in Example 1 of the present invention. Figure 1 It can be seen that the carbides are evenly distributed and fine, without obvious strip segregation; Figure 2 and Figure 3The rod structure is uniform, free of mixed crystals. The grain size at the center and edges of the rod is grade 8, with no grain size difference. The room-temperature tensile strength tested is 1375 MPa / 1391 MPa; the high-temperature tensile strength at 650°C is 1146 MPa / 1122 MPa. The high-temperature endurance at 650°C / 690 MPa is 63.5 hours / 68.5 hours, and the high-temperature endurance elongation is 8.6% / 9.1%.
[0047] Example 2
[0048] The present embodiment provides a 9.1 mm diameter small-size GH4169 high-temperature alloy bar, which includes the following components and their weight percentages: C: 0.028%; Si: 0.069%; Mn: 0.0055%; P: 0.008%; S: 0.0006%; Cr: 18.78%; Mo: 3.07%; Al: 0.574%; Ti: 1.03%; Nb: 5.21%; Ni: 52.40%; B: 0.0037%; Cu: 0.012%; Co: 0.035%; Ta: 0.0012%; Bi: 0.00001%; Pb: 0.0001%; Sn: 0.0001%; Se: 0.0001%; Ag: 0.0001%; Te: 0.00001%; TI: 0.0005%; Mg: 0.001%; Ca: 0.001%; O: 0.0005%; N: 0.0057%; the balance is Fe
[0049] The above-mentioned small-sized GH4169 high-temperature alloy bars are prepared by the following method: batching → vacuum induction melting → electroslag remelting → vacuum consumable remelting → ingot homogenization → ingot surface treatment to obtain qualified ingots; then forging → homogenization → hot rolling → hot rolling → solution annealing → primary cold drawing → finished product heat treatment → polishing and straightening → non-destructive testing.
[0050] The specific steps are as follows:
[0051] S1: A GH4169 high-temperature alloy ingot with an ingot diameter of φ508 mm was obtained by a triple smelting process of vacuum induction + electroslag remelting + vacuum consumable remelting;
[0052] S2: The GH4169 alloy ingot obtained in S1 was homogenized in a natural gas furnace by holding at 1150°C for 24 h and then heating to 1190°C for 60 h.
[0053] S3: The alloy ingot after S2 homogenization treatment is forged with an initial forging temperature of 1092°C and a final forging temperature of 961°C. After multiple forgings, a 130 mm square billet is finally obtained, which is then air-cooled.
[0054] S4: The billet after S3 forging is subjected to secondary homogenization treatment at a temperature of 1180°C and a holding time of 20 h;
[0055] S5: hot rolling the billet obtained in step S4 to a hot rolled billet of 45 mm square;
[0056] S6: The billet obtained in S5 is rolled in two passes using a horizontal rolling mill, with each pass being rolled in multiple passes. In the first pass, the billet is rolled from 45 mm square to φ18 mm. In the second pass, the billet is heated to a holding temperature of 1060°C for 30 min, followed by hot rolling. The total deformation is 72%, the rolling line speed is controlled at 1.60 m / s, the final rolling time is 32 s, the final rolling temperature is 1020°C, and the billet is air-cooled after final rolling to obtain a hot-rolled billet with a specification of φ9.5 mm.
[0057] S7: S6 was rolled to a semi-finished hot-rolled bar with a diameter of 9.5 mm. The bar was then held at 960°C in a solution furnace for 60 minutes, air-cooled, and then cold-drawn once using a fixed-die drawing machine at a drawing rate of 50 mm / s and a cold drawing deformation of 8.2%, resulting in a φ9.1 mm bar. The φ9.1 mm bar was aged by holding at 720°C for 8 hours, then cooling at a rate of 50°C / s to 620°C, holding at 620°C for 8 hours, and air-cooling.
[0058] The final φ9.1 mm rods were tested for carbide, grain size, room temperature and high temperature properties. Figures 4-6 As shown, Figure 4 This is the carbide distribution diagram of the φ9.1 mm rod prepared in Example 2 of the present invention. Figure 5 This is the grain size center distribution diagram of the φ9.1 mm rod prepared in Example 2 of the present invention. Figure 6 This is the grain size edge distribution diagram of the φ9.1 mm rod prepared in Example 2 of the present invention, Figure 4 It can be seen that the carbides are evenly distributed and fine, without obvious strip segregation; Figure 5 and Figure 6 The rod structure is uniform, free of mixed crystals. The grain size at the center and edges of the rod is grade 8, with no grain size difference. The room-temperature tensile strength is 1436 MPa / 1449 MPa; the high-temperature tensile strength at 650°C is 1150 MPa / 1156 MPa. The high-temperature endurance at 650°C / 690 MPa is 59.6 h / 79.9 h, and the high-temperature endurance elongation is 15.0% / 9.0%.
[0059] Comparative Example 1
[0060] Compared with the embodiment, the comparative example does not adopt the secondary homogenization treatment and cold drawing process. The comparative example adopts the process to provide a small-sized GH4169 high-temperature alloy bar with a diameter of 11 mm, which includes the following components and their weight percentages: C: 0.024%; Si: 0.063%; Mn: 0.011%; P: 0.012%; S: 0.0011%; Cr: 18.85%; Mo: 3.03%; Al: 0.59%; Ti: 1.03%; Nb: 5.39%; Ni: 52.58%; B: 0.0031%; Cu: 0.015%; Co: 0.023%; Ta: 0.005%; Bi: 0.00001%; Pb: 0.0001%; Sn: 0.00009%; Se: 0.0001%; Ag: 0.0001%; Te: 0.00001%; TI: 0.0005%; Mg: 0.001%; Ca: 0.001%; O: 0.0006%; N: 0.0034%; the balance is Fe
[0061] The small-sized GH4169 superalloy bar was prepared by the following process: batching → vacuum induction melting → electroslag remelting → vacuum consumable remelting → ingot homogenization → ingot surface treatment to obtain a qualified ingot. The ingot was then forged → hot rolling → hot rolling → finished product heat treatment → polishing and straightening → non-destructive testing. Unlike the examples, this comparative example did not employ secondary homogenization or cold drawing.
[0062] The specific steps are as follows:
[0063] S1: A GH4169 high-temperature alloy ingot with an ingot diameter of φ508 mm was obtained by a triple smelting process of vacuum induction + electroslag remelting + vacuum consumable remelting;
[0064] S2: The GH4169 alloy ingot obtained in S1 was homogenized in a natural gas furnace by holding at 1150°C for 24 h and then heating to 1190°C for 60 h.
[0065] S3: The alloy ingot after S2 homogenization treatment is forged with an initial forging temperature of 1096°C and a final forging temperature of 958°C. After multiple forgings, a 130 mm square billet is finally obtained, which is then air-cooled.
[0066] S4: hot rolling the billet obtained in step S3 to a hot rolled billet of 45 mm square;
[0067] S5: The billet obtained in S4 is rolled in two passes using a horizontal rolling mill, with each pass being rolled in multiple passes. In the first pass, the billet is rolled from 45 mm square to φ20 mm. In the second pass, the billet is heated to a holding temperature of 1060°C for 30 min, followed by hot rolling. The total deformation is 70%, the rolling line speed is controlled at 1.62 m / s, the final rolling time is 37 s, the final rolling temperature is 1011°C, and the billet is air-cooled after final rolling to obtain a hot-rolled billet with a specification of φ11 mm.
[0068] S6: S5 was rolled into a semi-finished hot-rolled bar of φ11 mm, which was then held at 960°C in a solution furnace for 60 min and air-cooled to obtain a φ11 mm bar. The φ11 mm bar was aged by holding at 720°C for 8 h, then cooling to 620°C at a rate of 50°C / s, holding at 620°C for 8 h, and air-cooling.
[0069] The final φ11 mm rods were tested for carbide, grain size, room temperature and high temperature properties. Figures 7 and 8 As shown, Figure 7 This is the carbide distribution diagram of the φ11 mm rod prepared in Comparative Example 1 of the present invention. Figure 8 This is the center distribution diagram of the grain size of the φ11 mm rod prepared in Comparative Example 1 of the present invention. Figure 9 This is the grain size edge distribution diagram of the φ11 mm rod prepared in Comparative Example 1 of the present invention. Figure 7 It can be seen that its carbides are distributed in obvious stripes; Figure 8 and Figure 9 It can be seen that the grains in the center and edges of the rod are fine and the grain size reaches more than 10 levels. The overall grain size of the rod has a difference of more than 2 levels. The room temperature tensile strength is 1370 MPa / 1461 MPa; the high temperature tensile strength at 650℃ is 967 MPa / 1146 MPa; the high temperature endurance at 650℃ / 690 MPa is 23.6 h / 54.9 h, and the high temperature endurance elongation is 4.9% / 8.5%. It can be seen that after the process of Comparative Example 1 is implemented, the rod structure not only has a grain size difference of more than 2 levels, but also because the cold drawing process and secondary homogenization treatment are not used, the amount of δ phase precipitation in the rod is small and the carbide aggregation area is fine-grained banded structure. The mechanical properties at room temperature and high temperature fluctuate greatly, and the endurance notch sensitivity is observed. The high temperature endurance elongation even fails to meet the internal control.
[0070] Comparative Example 2
[0071] Comparative Example 2 Compared with the embodiment, Comparative Example 2 adopts the conventional rolling GH4169 process, and does not control the final deformation. The process provides a small-size GH4169 high-temperature alloy bar with a diameter of 10.5 mm, including the following components and their weight percentages: C: 0.031%; Si: 0.08%; Mn: 0.005%; P: 0.0062%; S: 0.0009%; Cr: 19.03%; Mo: 3.16%; Al: 0.673%; Ti: 0.904%; Nb: 5.10%; Ni: 51.12%; B: 0.0041%; Cu: 0.0072%; Co: 0.005%; Ta: 0.0042%; Bi: 0.00001%; Pb: 0.0001%; Sn: 0.0001%; Se: 0.0001%; Ag: 0.0001%; Te: 0.00001%; TI: 0.0005%; Mg: 0.001%; Ca: 0.001%; O: 0.0007%; N: 0.0061%; the balance is Fe.
[0072] The above-mentioned small-sized GH4169 high-temperature alloy bars are prepared by the following method: batching → vacuum induction melting → electroslag remelting → vacuum consumable remelting → ingot homogenization → ingot surface treatment to obtain qualified ingots; then forging → homogenization → hot rolling → hot rolling → solution annealing → primary cold drawing → finished product heat treatment → polishing and straightening → non-destructive testing.
[0073] The specific steps are as follows:
[0074] S1: A GH4169 high-temperature alloy ingot with an ingot diameter of φ406 mm was obtained by a triple smelting process of vacuum induction + electroslag remelting + vacuum consumable remelting;
[0075] S2: The GH4169 alloy ingot obtained in S1 was homogenized in a natural gas furnace by holding at 1150°C for 20 h and then heating to 1190°C for 30 h.
[0076] S3: The alloy ingot after S2 homogenization treatment is forged with an initial forging temperature of 1100°C and a final forging temperature of 958°C. After multiple forgings, a 130 mm square billet is finally obtained, which is then air-cooled.
[0077] S4: The billet after S3 forging is subjected to secondary homogenization treatment, the homogenization temperature is 1170℃, and the holding time is 15 h;
[0078] S5: hot rolling the billet obtained in step S4 to form a hot rolled billet of 55 mm square;
[0079] S6: The billet obtained in S5 is rolled in two passes using a horizontal rolling mill, with each pass being rolled in multiple passes. In the first pass, the square is rolled from 55 mm to 31 mm. In the second pass, the total deformation is 90%. The rolling line speed is controlled at 1.5 m / s, the final rolling temperature is 967°C, and air cooling is performed after final rolling to obtain a hot-rolled bar with a specification of φ11 mm.
[0080] S7: The semi-finished hot-rolled bar billet of S6 was rolled to φ11 mm and held at 960°C in a solution furnace for 60 min. It was then air-cooled and then cold-drawn once using a fixed die drawing machine at a drawing rate of 50 mm / s and a cold drawing deformation of 8.5% to obtain a φ10.5 mm bar. The φ10.5 mm bar was aged by holding at 720°C for 8 h, then cooling to 620°C at a rate of 50°C / s, holding at 620°C for 8 h, and air-cooling.
[0081] The grain size of the final φ10.5 mm bar was tested. Figure 10 As shown, Figure 10 This is the grain size edge distribution diagram of the φ10.5 mm rod prepared in Comparative Example 2 of the present invention, Figure 10 It can be seen that the rod structure is uniform and there is no mixed crystal, but the grain size at the center and edge of the rod reaches above level 11, which cannot meet the user's grain size requirement of level 6-9.
[0082] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing GH4169 high temperature alloy bar, characterized in that: The following steps are involved: S1) sequentially subjecting a GH4169 high temperature alloy ingot to a first homogenization treatment, forging, a second homogenization treatment, and hot rolling to obtain a billet; S2) performing a first heat rolling and a second heat rolling on the billet obtained in step S1) to obtain a billet; The second-fire rolling specifically comprises: holding the billet after the first-fire rolling at a temperature of 1020° C. to 1100° C. for 30 min to 40 min and then rolling it; the total deformation of the second-fire rolling is 60% to 75%, the second-fire rolling time is within 40 s, the second-fire rolling speed is 1.4 m / s to 1.8 m / s, and the final rolling temperature of the second-fire rolling is above 1000° C.; S3) subjecting the bar blank obtained in step S2) to solution treatment, primary cold drawing, and aging treatment in sequence to obtain a GH4169 high-temperature alloy bar; The drawing rate of the primary cold drawing is 45 mm / s to 55 mm / s, and the deformation of the primary cold drawing is 5% to 10%.
2. The preparation method according to claim 1, characterized in that In step S1), the GH4169 high-temperature alloy ingot is obtained by sequentially subjecting raw materials to vacuum induction melting, electroslag remelting and vacuum consumable remelting.
3. The preparation method according to claim 1, characterized in that In step S1), the first homogenization treatment is specifically: keeping the temperature at 1140°C to 1160°C for 10 h to 24 h, then heating to 1180°C to 1200°C and keeping the temperature for 24 h to 72 h; The second homogenization treatment specifically includes: keeping the temperature at 1170° C. to 1190° C. for 10 h to 20 h.
4. The preparation method according to claim 1, characterized in that In step S1), the initial forging temperature of the forging is not lower than 1080°C, and the final forging temperature of the forging is not lower than 950°C.
5. The preparation method according to claim 1, characterized in that In step S1), the blank obtained after hot rolling is a blank of 45 mm square to 55 mm square; In step S3), a GH4169 high-temperature alloy bar with a specification of φ8 mm to φ12 mm is obtained.
6. The preparation method according to claim 1, characterized in that In step S3), the temperature of the solution treatment is 950° C. to 980° C., and the time of the solution treatment is 50 min to 70 min.
7. The preparation method according to claim 1, characterized in that In step S3), the aging treatment is specifically as follows: keeping the temperature at 700°C-750°C for 7 h-9 h, cooling the temperature to 600°C-650°C at a cooling rate of 45°C / s-55°C / s and keeping the temperature for 7 h-9 h.
8. The preparation method according to claim 1, characterized in that In step S3), the GH4169 high-temperature alloy bar comprises the following components in weight percentage: C: 0.015%~0.060%; Si: ≤0.35%; Mn: ≤0.35%; P: ≤0.015%; S: ≤0.002%; Cr: 17.00%~21:00%; Mo: 2.80%~3.30%; Al: 0.30%~0.70%; Ti: 0.75% ~1.15%; Nb: 5.00%~5.50%; Ni: 50.00%~55.00%; B: 0.002%~0.006%; Cu: ≤0.30%; Co: ≤1.00%; Ta: ≤0.10%; Bi: ≤0.00003%; Pb: ≤0.0005%; Sn : ≤0.005%; Se: ≤0.0003%; Ag: ≤0.0005%; Te: ≤0.00005%; TI: ≤0.0001%; Mg: ≤0.005%; Ca: ≤0.005%; O: ≤0.005%; N: ≤0.01%; the balance is Fe.
9. GH4169 high-temperature alloy rod obtained by the preparation method according to any one of claims 1 to 8.
10. An aerospace fastener, characterized in that: The invention is obtained by using the GH4169 high-temperature alloy bar obtained by the preparation method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Manufacturing method for producing high-temperature alloy GH4169 fine-grained bar through combined high-speed and radial forging
CN106868436A
A GH738 alloy bar and its preparation method
CN116804261A
GH4141 high-temperature alloy bar and preparation method thereof
CN118007044A
GH4080A high-temperature alloy bar and preparation method thereof
CN118751715A
Cited By
Preparation process of 140ksi steel grade high-strength UNS N07718 alloy bar
CN120905562A
